Opioids in the USA: Disparities in Addiction and Incarceration. Issue 5 (4th October 2019) - Kazemi, Arianna; Kennedy, Connor; Silverman, Gabri; Reich, Nicholas G.
Abstract: Arianna Kazemi, Connor Kennedy and Gabri Silverman, undergraduate winners of the ASA Public Health Data Challenge, and their advisor Nicholas G. Reich, explore differences in the death, arrest and reoffending rates for opioid users in the USA